The effect of six weeks high intensity interval training on protein expression of Melanocortin 1 Receptor of monocytes and plasma levels of Alpha melanocyte stimulating hormone in overweight men - سید محسن آوندی; خسرو ابراهیم; علیرضا سلیمی; مهدی هدایتی (Shahid Beheshti University, 2012)
Objectives: The purpose of this study is to investigate the effect of six weeks high intensity interval training (HIT)on protein expression of Melanocortin 1 Receptor (MC1R) of monocytes and plasma levels of melanocytestimulating hormone alpha (∝-MSH) in overweight men. Methodology: Twenty sedentary overweight students withaverage age of 25.2 ± 1.88 years, Vo2max 41.9 ± 4.28 ml.kg-1.min-1, Body fat 25.6±3.1 percent and BMI 27.3± 1.63kg/m² were randomly assigned to HIT (n=10) and control (n=11) group. Fasting blood samples, body fat percentageand BMI measurement were taken before and after 6 weeks of training. HIT group complete 8 intervals (300 meterwith %100-110 vVO2max and rest interval ratio 2-1) on the treadmill for 3 d/wk and for 6 weeks that every twoweek one interval and five percent adds to training intensity and the control group had no activity during the test.Diet of subject was control before begin the study. Results: ANOVA with repeated measures indicated body fatpercentage (P=0.001), body weight (P=0.002), and BMI (P=0.005) significantly decreased and protein expression ofMC1R of monocytes increased significantly (P=0.001) in the HIT group after 6 weeks of training. Althoughincrement in ∝-MSH was non-significant in the experimental group after 6 weeks of training. Conclusions: HITtraining increased protein expression of MC1R of monocytes significantly in overweight individuals and may beimportant in the prevention and control of inflammation and chronic diseases in overweight men by development ofanti-inflammatory effects by MC1R. We suggest further research into the effect of HIT by overweight individualson ∝-MSH and MC1R levels are conducted with large population samples and the protocols outlined in the currentstudy.